Continuous Dependence for the Pseudoparabolic Equation. (23rd August 2010) - Yaman Yaman, M. M.; Gür Gür, Ş. Ş.
Abstract : We determine the continuous dependence of solution on the parameters in a Dirichlet-type initial-boundary value problem for the pseudoparabolic partial differential equation.